2021
DOI: 10.26811/peuradeun.v9i2.530
|View full text |Cite
|
Sign up to set email alerts
|

The The Mediating Effect of Employee Loyalty on the Relationship Between Job Satisfaction and Organizational Performance

Abstract: One of the key factors for sustaining an organizational performance for any organization is maintaining loyalty and retention of skilled and experienced employees. Therefore, revealing positive and negative factors impacting employee loyalty and taking action for further improvement has been an essential aspect for organizations. The current paper aims at researching how employee satisfaction has an impact on employee loyalty as well as the organizational performance of the organization based on the case of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…As far as the effect on anxiety and depression is concerned, it leads to an inclination to depression, anxiety, feelings of unhappiness, irritability, absence of a sense of humour, and a subjective feeling of failure. The associations mentioned have been independently confirmed in various studies, including the works of Lange et al (2020) and Zanabazar et al (2023). On the other hand, work-related bullying had the strongest effect on wellbeing and activity, which decreases the individual sense of satisfaction, self-confidence, good mood, and feelings of strength and energy.…”
Section: Discussionmentioning
confidence: 70%
“…As far as the effect on anxiety and depression is concerned, it leads to an inclination to depression, anxiety, feelings of unhappiness, irritability, absence of a sense of humour, and a subjective feeling of failure. The associations mentioned have been independently confirmed in various studies, including the works of Lange et al (2020) and Zanabazar et al (2023). On the other hand, work-related bullying had the strongest effect on wellbeing and activity, which decreases the individual sense of satisfaction, self-confidence, good mood, and feelings of strength and energy.…”
Section: Discussionmentioning
confidence: 70%
“…PWG is a tie via which to build a friendship between employees ( Ellwardt et al, 2012b ), and an effective means to promote teamwork and job satisfaction. Previous studies found that job satisfaction would make a difference to employees’ working behavior, attitude, and organizational performance via the mediating role of employee loyalty ( Phuong and Vinh 2020 ; Zanabazar and Jigjiddorj 2021 ). This study has arrived at the similar conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…Frequent employee turnover can put the company in an awkward position, such as profit cuts, and affect the work efficiency and mental state of other employees within the company ( Phuong and Vinh 2020 ). Therefore, employee loyalty plays an important role in formulating precise organizational development policies and achieving organizational goals ( Zanabazar and Jigjiddorj 2021 ). Some studies point out it takes a cost equivalent to 6–9 months of emoluments to recruit, train, and orient a new employee ( Beehner and Blackwell 2016 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In the context of a significant impact on the organization's performance, the following non-financial measures were analyzed: organizational capabilities [15], system thinking [16], change capacity [10], [17], [18]. Other non-financial measures associated with organizational performance highlighted during the researches were among others: intellectual capital [19], job satisfaction [20], [21], employee performance [21], [22], [23], [24] and job performance [25], [26], [27].…”
Section: Theoretical Background For Organizational and Job Performanc...mentioning
confidence: 99%